2002
DOI: 10.15517/rbt.v55i1.6076
|View full text |Cite
|
Sign up to set email alerts
|

Distribución y abundancia de la ascidia Ecteinascidia turbinata (Ascidiacea: Perophoridae) en Cuba

Abstract: Distribution and abundance of the ascidian Ecteinascidia turbinata (Ascidiacea: Perophoridae) in Cuba. Permanently submerged mangrove roots (Rhizophora mangle) are the main habitat of the ascidian Ecteinascidia turbinata in Cuba. It was occasionally found on black coral (Antiphates caribeana) between 22 and 38 meters deep. This species exhibits a wide distribution in all the mangrove keys surrounding the Island of Cuba but does not occur in riparian or fringing mangroves. Populations of this species are abunda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Colony colour may be determined by environmental factors as it has been noted that the colour of E. thurstoni colonies was dependent on the available light with poor illumination resulting in colourless animals (Por & Dor 1975). The natural situation in which E. turbinata is found in its Caribbean range and in the Red sea, is the submerged roots of mangrove trees where ambient conditions are similar to those found in the SS 'Margit' site in Kalkara Creek, where low light levels were caused by a high silt sediment burden with relatively high temperatures; however, in Cuba it is also found in clean water attached to hard coral between 22 and 38 metres depth (Hernández-Zanuy et al, 2007), which is closer to the conditions found in St George's Bay and on the 'Tug 2' wreck (Table 1). E. turbinata is also found on wrecks in Bermuda (Berrill, 1932).…”
Section: Classification Of E Turbinatamentioning
confidence: 99%
“…Colony colour may be determined by environmental factors as it has been noted that the colour of E. thurstoni colonies was dependent on the available light with poor illumination resulting in colourless animals (Por & Dor 1975). The natural situation in which E. turbinata is found in its Caribbean range and in the Red sea, is the submerged roots of mangrove trees where ambient conditions are similar to those found in the SS 'Margit' site in Kalkara Creek, where low light levels were caused by a high silt sediment burden with relatively high temperatures; however, in Cuba it is also found in clean water attached to hard coral between 22 and 38 metres depth (Hernández-Zanuy et al, 2007), which is closer to the conditions found in St George's Bay and on the 'Tug 2' wreck (Table 1). E. turbinata is also found on wrecks in Bermuda (Berrill, 1932).…”
Section: Classification Of E Turbinatamentioning
confidence: 99%
“…On the other hand, several larval characters like the aforementioned horizontal larval tail, but also the large larval body size, or the larval papillae that are arranged in the sagittal plane, are similar to characters found in most aplousobranch larvae (e.g., Kott 1985Kott , 1990). In addition, Perophoridae are curious within the Phlebobranchiata, because the adults reproduce asexually and form clones connected by stolons, in which individuals brood the fertilized eggs until the fully developed larvae hatch (Van Name 1945;Hernández-Zanuy et al 2000). All these life-history traits are shared between perophorids and aplousobranchs.…”
Section: Introductionmentioning
confidence: 99%